Developing a model of sexual satisfaction based on cognitive factors (shared sex, difficulty in emotional regulation, differentiation), social (trust in interpersonal relationship), moral (moral justice) - Khabiri Pooya, Avisa; Mohammadi, Mohsen; Karami, Abolfazl; Rahimian Boogar, Ishagh (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The main purpose of this study is to develop a model of sexual satisfaction based on cognitive, social and moral factors, and to clarify the importance of these factors in improving the quality of sexual satisfaction of healthier people. Method: This research is a structural equation in terms of applied purpose and descriptive method. The statistical population of this study included 300 people (129 men and 161 women) married and single who had sexual experience and ranged from diploma to doctorate. Data were obtained using Sexual Satisfaction Questionnaire, Adjustment Difficulties Questionnaire, Sexuality Questionnaire, Differentiation Scale Questionnaire, Interpersonal Trust Questionnaire and Moral Justice Questionnaire. All information obtained from this study was analyzed by SPSS software version 22 based on descriptive statistics such as frequency, mean and standard deviation and the path analysis method was used. Results: The results showed that sexual satisfaction with shared sex according to the value of 0.427 with difficulty of emotional regulation to the value of 0.258, with differentiation to the value of 0.243, trust in interpersonal relationship to the value of 0.269, Moral justice in the amount of 0.175 is seen with sexual satisfaction. Conclusion: Individual and interpersonal dimensions of human beings can affect sexual satisfaction. It is suggested that the necessary training be done according to different human dimensions in the form of a model that focuses on cognitive issues, interpersonal relationships and moral dimension and provide conditions for promoting sexual satisfaction and its continuation in a safe and healthy environment to continue. This route will help.